Rock Salt Properties for Gas Storage in Mined Caverns: Part I–Short-Term Deformation and Yield, Long-Term Creep, and Gas Sealing Capacity - J. Sarout; M. Sari; L. Esteban; P. P. Mandal; J. Bourdet; D. Nguyen; J. Strand; E. Frery; L. Imbert; A. Francois; L. Langhi; D. Mallants (Rock Mechanics and Rock Engineering, 2026)
Deep rock salt formations can be drilled and solution-mined into caverns for permanent waste disposal, or temporary energy storage (natural gas/compressed air/hydrogen) to alleviate the intermittency of wind/solar energy. We report here the results of the laboratory appraisal of the key properties of a thick Devonian rock salt formation in the Canning Basin (Western Australia). Two representative but contrasting lithofacies were identified: a clean lithofacies made of nearly pure halite, and a dirty lithofacies comprising anhydrite, and dolomite/quartz inclusions. On each lithofacies, we conducted a mineralogical, microstructural and petrophysical characterisation, and a long-term four-stage triaxial test to simulate the impact of depth and anthropogenic stress perturbations. Strains and ultrasonic P-/S-wave velocities were monitored, and at specific stages of the triaxial test, long-term gas transmissivity and creep tests were conducted for up to 16 and 42 days, respectively. At all the triaxial stresses explored, including the in-situ conditions, the oven-dry clean salt facies exhibits a typical gas permeability of 5.10 –5 mD = 5.10 –20 m 2 , whereas the dirty salt is 100 to 1000 times more permeable to gas. The estimated steady-state creep rates are consistent with the extensive collection of literature data also reported here. The dominant creep mechanism is likely dislocation glide, complemented by frictional sliding where damage might exist. Pressure-solution creep is probably not dominant here, especially within the testing time scale. However, water is likely present in deep salt bodies and around man-made salt caverns, promoting overall creep through pressure-solution, and damage healing, hence reducing gas permeability even further.

Beach litter sources around Nuuk, Greenland: An analysis by UArctic summer school graduate course students - Marthe Larsen Haarr; Lis Bach; Catherine P. Chambers; Jannike Falk-Andersson; Thomas Juul-Pedersen; Ryan d'Arcy Metcalfe; Anna Sinisalo; Jakob Strand; Helene Svendsen; Julia E. Baak; Helga Hvanndal Björnsdóttir; Elsa Margaret Krook Brenner; et al. (Marine Pollution Bulletin, 2023)

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

Diversity, divergence and density: How habitat and hybrid zone dynamics maintain a genomic cline in an intertidal barnacle - John P. Wares; Allan E. Strand; Erik E. Sotka (Journal of Biogeography, 2021)
Aim As within‐species genomic data have been shown useful in interpreting broader biogeographic trends, we analysed the mode of population genomic isolation involved in a well‐studied intertidal genomic cline to better understand the mechanisms maintaining it. These results were interpreted in the context of spatial variation in habitat use and availability as well as likely fitness consequences for hybridization between the two lineages. Location Pacific coast of North America. Taxon Arthropods (Class Maxillopoda, Order Sessilia, Family Balanidae; Balanus glandula ). Methods Genotype‐by‐sequencing approaches were used to generate single‐nucleotide polymorphism markers across sites sampled between southern Alaska and Southern California. Inference using standard population genomic methods, including analysis of population structure, inbreeding and linkage disequilibrium, was used to identify the steepest transitions across the largest number of loci examined. These data were put in the context of observed population density and habitat availability. Results We show that the majority of markers analysed show strong clinal transitions in a very narrow portion of the California coast. Patterns of linkage disequilibrium among markers, along with prior evidence of variation in reproductive potential by latitude and by mitochondrial lineage, suggest some reproductive isolation among the northern and southern lineages of B. glandula that are concordant with the drop in population density and habitat availability in central California. Main Conclusions A significant clinal transition in genomic diversity is stronger and more localized than previously recognized and exhibits statistical patterns suggesting that the lineages are reproductively and phenotypically distinct in ways that may be ecologically important. As this species has been used to infer process in coastal biogeography, further study of concordant patterns will be important for advancing our understanding of this region.

Lessons from the First Generation of Marine Ecological Forecast Products - Mark R. Payne; Alistair J. Hobday; Brian R. MacKenzie; Desiree Tommasi; Danielle P. Dempsey; Sascha M. M. Fässler; Alan C. Haynie; Rubao Ji; Gang Liu; Patrick D. Lynch; Daniela Matei; Anna K. Miesner; et al. (Frontiers in Marine Science, 2017)

A global database of nitrogen and phosphorus excretion rates of aquatic animals - Michael J. Vanni; Peter B. McIntyre; Dennis Allen; Diane L. Arnott; Jonathan P. Benstead; David J. Berg; Åge Brabrand; Sébastien Brosse; Paul A. Bukaveckas; Adriano Caliman; Krista A. Capps; Luciana S. Carneiro; et al. (Ecology, 2017)
Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology ( MTE ) and ecological stoichiometry ( ES ). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10,534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES , as described in Vanni and McIntyre (2016; Ecology DOI : 10.1002/ecy.1582 ).

Mammalian cytochrome CYP2E1 triggered differential gene regulation in response to trichloroethylene (TCE) in a transgenic poplar - Jun Won Kang; Hui-Wen Wilkerson; Federico M. Farin; Theo K. Bammler; Richard P. Beyer; Stuart E. Strand; Sharon L. Doty (Functional & Integrative Genomics, 2010)

Analysis and comparison of the microbial community structures of two enrichment cultures capable of reductively dechlorinating TCE and cis ‐DCE - April Z. Gu; Brian P. Hedlund; James T. Staley; Stuart E. Strand; H. David Stensel (Environmental Microbiology, 2004)
Summary In order to study the effect of different chloroethenes (electron acceptors) on the bacterial composition of dechlorinating communities, two reductive dechlorinating enrichment cultures were developed that were able to reduce trichloroethene (TCE) and cis ‐1,2‐dichloroethene ( cis ‐DCE) to ethene using hydrogen as electron donor, respectively. The inoculum for the cultures was material from a methanogenic fluidized bed reactor (FBR), which was originally seeded with digester sludge and showed a stable capacity for tetrachloroethene (PCE) reduction to ethene for over six years. Molecular methods were used to determine and compare the microbial communities of these two enrichment cultures. A clone library of bacterial 16S rRNA genes was generated for each enrichment. The clones were screened into different groups by restriction fragment length polymorphism (RFLP) analysis using two different four base pair recognition restriction enzymes. A total of 12 sequence types were identified by phylogenetic analysis of nearly complete 16S rDNA sequences (∼1450 bp). The sequences were affiliated with six recognized phyla of the domain Bacteria: Firmicutes (low G+C Gram‐positives), Chloroflexi (green non‐sulphur bacteria), Actinobacteria (high G+C Gram‐positives), Bacteroidetes (Cytophaga‐Flexibacter‐Bacteroides), Nitrospira and Spirochaetes. The results led to the identification of an organism closely related to Dehalococcoides ethenogenes to be the presumptive dechlorinator in both enrichments. Different electron acceptors affected the bacterial diversity and the community profiles of the two enrichments. Most of the sequences identified in our dechlorinating enrichments shared high similarities with sequences previously obtained from other enriched dechlorinating cultures and chlorinated‐compound‐contaminated sediments or aquifers, suggesting these bacteria may have direct or indirect roles in reductive dechlorination.

Examples of high-frequency EPR studies in bioinorganic chemistry - K. Kristoffer Andersson; Peter P. Schmidt; Bettina Katterle; Kari R. Strand; Amy E. Palmer; Sang-Kyu Lee; Edward I. Solomon; Astrid Gräslund; Anne-Laure Barra (JBIC Journal of Biological Inorganic Chemistry, 2003)

Mechanism of aerobic transformation of carbon tetrachloride by poplar cells - Xiaoping Wang; Milton P. Gordon; Stuart E. Strand (Biodegradation, 2002)

Synthesis of theoretical and empirical experiences from nutrient and cyprinid reductions in Lake Ringsjön - E. Bergman; L.-A. Hansson; A. Persson; J. Strand; P. Romare; M. Enell; W. Granéli; J. M. Svensson; S. F. Hamrin; G. Cronberg; G. Andersson; E. Bergstrand (Hydrobiologia, 1999)